Experience in applying the strategy of simultaneous selective perfusion of the brain, heart and lower body in reconstruction of the aortic arch in infants - V. V. Bazylev; K. T. Shcheglova; N. N. Artemyev; A. I. Magilevets; A. A. Shikhranov; M. V. Kokashkin; N. E. Makogonchuk; D. A. Bofanov (Вестник анестезиологии и реаниматологии)
Relevance. The choice of perfusion strategy is vital for the protection of internal organs during surgery. In several studies of recent years, as well as by us, a strategy of sustained total all region (STAR) perfusion (selective brain, heart and lower body perfusion) has been proposed, allowing to avoid ischemic and reperfusion injuries of internal organs.The objective was to evaluate the benefits of STAR perfusion during reconstruction of the aortic arch in children.Materials and methods. The prospective study included 15 patients who underwent aortic arch reconstruction using a strategy of simultaneous selective brain, heart and lower body perfusion (STAR perfusion) in the period from June 2022 to May 2023. The average age at the time of surgery was 1.3 months (95 % CI (confidence interval) 6.0–16.0), the average body weight was 3.4 kg (95 % CI 2.7–4.1).Results. Сhanges of the tissue oximetry index, measured at two points, did not fall below reference ranges at any stage of the operation. The greatest mean value of lactate concentration during the operation was 2.8 ± 1.0 mmol/l, recovery of the indicator was noted after 6 hours – 1.9 ± 0.9 mmol/l. Kidney function evaluation – the rate of diuresis and creatinine levels did not exceed reference levels. The average treatment time in the intensive care unit was 7.7 ± 4.3 days (95 % CI 4.5 10.9), in the hospital – 15.4 ± 5.8 days (95 % CI 11.4–19.4). There were no deaths among those operated using the new perfusion strategy.Conclusion. The use of the strategy of Sustained Total All Region (STAR) perfusion in case of reconstruction of the aortic arch in newborn, infants and young children is safe and advanced, since it avoids ischemia of internal organs and reduces the risk of post-ischemic complications.